"Our Shtetl, Tel Aviv, Must and Will Become the Metropolis of Yiddish": Tel Aviv—a Center of Yiddish Culture?. Issue 1 (24th April 2017) - Bar-Am, Gali Drucker
Abstract : The remnant of the eastern European Jews that arrived in Israel after the Holocaust established a vibrant center of Yiddish culture in Tel Aviv. This paper tells its story. It spotlights the uniqueness of the Tel Aviv center in comparison with similar cultural centers established by eastern European Jews in other cities around the world, both before and after the Holocaust. It portrays the Jewish cultural activists and leaders that composed the Tel Aviv Yiddish center, the special conditions that awaited them in Israel, the institutions that they established, and their aftermath. Finally, it considers the Tel Aviv Yiddish cultural center as a test case for examining the social role of the Jewish cultural center after the Holocaust.